2019
DOI: 10.1002/advs.201901904
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Butyrylcholinesterase Inactivation and Reactivation by Polymer‐Based Protein Engineering

Abstract: Organophosphate nerve agents rapidly inhibit cholinesterases thereby destroying the ability to sustain life. Strong nucleophiles, such as oximes, have been used as therapeutic reactivators of cholinesterase‐organophosphate complexes, but suffer from short half‐lives and limited efficacy across the broad spectrum of organophosphate nerve agents. Cholinesterases have been used as long‐lived therapeutic bioscavengers for unreacted organophosphates with limited success because they react with organophosphate nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 77 publications
0
30
0
Order By: Relevance
“…If rates of reactivation and inhibition are consistent, the enzyme and the reactivator could act as effective pseudo‐catalytic bioscavengers. In 2020, Zhang et al 81 connected BChE and oxime (1:1) by polymer to locally increase the concentration of reactivators. The BChE‐polymer‐oxime conjugates were insensitive to the inhibition of OPs and therefore extended the active time of BChE.…”
Section: The Role Of Bche In Detoxifying Opsmentioning
confidence: 99%
“…If rates of reactivation and inhibition are consistent, the enzyme and the reactivator could act as effective pseudo‐catalytic bioscavengers. In 2020, Zhang et al 81 connected BChE and oxime (1:1) by polymer to locally increase the concentration of reactivators. The BChE‐polymer‐oxime conjugates were insensitive to the inhibition of OPs and therefore extended the active time of BChE.…”
Section: The Role Of Bche In Detoxifying Opsmentioning
confidence: 99%
“…We have recently reported that oximes that have been coupled to polymer backbones via click chemistry can reactivate OP-inhibited cholinesterases 15 . We were therefore interested in whether a family of newly synthesized clickable alkyne-oximes (chemical structures are shown in Supplementary Scheme 6 ), derived from the HTS-identified leads, would also reactivate the inhibited enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…In order to bridge this PK gap, we are interested in the direct conjugation of oximes to polymers. Such protein polymer–oxime conjugates were recently synthesized in our lab 15 . These polymer–oxime adducts tethered covalently to BChE by the atom transfer radical polymerization (ATRP) process were shown to reactivate OP-inhibited BChE by inter- and intramolecular interactions 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Phosphotriesterases (PTE) of various origins, in particular, can be used for detection of OPs [13], decontamination and remediation [8,[14][15][16][17][18] and for therapy of OP poisoning as catalytic bioscavengers [7,[19][20][21][22]. Because OPs are hemi-substrates of ChEs, research of novel human ChE mutants capable of hydrolyzing OPs is of great interest for improving catalytic bioscavenger-based medical countermeasures of OP poisoning [23][24][25] and implementation of pseudocatalytic bioscavenger systems composed of ChE-reactivator [26][27][28]. Enzymatic hydrolysis of P-S bonded OPs, such as V-agents, is currently monitored by the reaction of the OP thiol leaving group with DTNB [16,29].…”
Section: Introductionmentioning
confidence: 99%